Seismic Analysis of Coupled High-Speed Train-Bridge with the Isolation of Friction Pendulum Bearing - Xinmin Hong; Wenhua Guo; Zihao Wang (Advances in Civil Engineering)
The paper presents a framework for the seismic analysis of the coupled high-speed train-bridge with the isolation of friction pendulum bearing (FPB). Taking the rail irregularities as system’s self-excitation with the seismic as external excitation, the equation of motion of the train-bridge coupled system under earthquake is built up. A five-span simple-supported railway bridge is taken as an example, and the computer simulation method is used to establish the dynamic model of the train-bridge system with the isolation of FPB under earthquake. A train composed of eight 4-axle coaches of 35 degrees-of-freedom (DOF) is considered, and FPB is simulated by a force element which includes both nonlinear spring and damper characteristics and a hysteresis function. Backward differentiation formula and the mode superposition method are adopted in the calculation of coupling vibration of the train-bridge system. The dynamic responses of the train running on the bridge with the isolation of FPB and with the common spherical bearing (CSB) under earthquake are studied. The results show that FPB with a friction coefficient no less than 0.05, instead of CSB, can reduce the dynamic response of the train greatly; the faster the train speed and the higher the pier, the greater the effect of FPB. However, FPB may increase the dynamic response of the train when the seismic intensity exceeds 0.14 g.